Bi-Level Optimal Scheduling Strategy of Integrated Energy System Considering Adiabatic Compressed Air Energy Storage and Integrated Demand Response - Men, Jiakai (Journal of electrical engineering & technology, 2024)
Aiming at the energy consumption and economic operation of the integrated energy system (IES), this paper proposes an IES operation strategy that combines the adiabatic compressed air energy storage (A-CAES) device and the integrated demand response (IDR) theory with the two-layer optimization model, and comprehensively considers the interaction between the planning and operation of two different time scales. The improved two-level optimal scheduling method in this paper takes IES operators and users as different subjects, and coordinates the output of multiple energy sources on the basis of meeting IES constraints to minimize the cost. The upper layer is the energy network system. The introduced IDR theory participates in the upper layer planning to improve the operation reliability and economy of IES and reduce the total network cost under the IES configuration. The lower layer is the energy hub system. The added A-CAES device is used to improve the imbalance of energy supply and demand of IES and reduce the operation cost of the lower layer power grid. First of all, under the IES framework with electricity, gas and heat as the main demand, preliminary investigation and statistics are conducted on the energy demand of various loads. Secondly, the IES two-layer scheduling model is established. The objective function of economic dispatch is to minimize the operation cost. The CPLEX tool kit of GAMS software is used to solve the problem. Finally, a simulation example shows that the improved two-level optimal scheduling model can effectively restrain the frequent adjustment of unit output caused by load fluctuation. IES operation cost can be effectively reduced by 5.3%. This two-layer optimization model can improve energy utilization, reduce operation cost, improve the accuracy of scheduling plan, and achieve low-carbon economic operation.